Police basic firearms training: a decontextualised preparation for real-life armed confrontations - Henriksen, Steinar Vee (Policing and society, 2021)
The purpose of this study is to compare the basic firearms training delivered by the police (university) colleges in New Zealand and Norway, and how this training reflects experience from real-life armed confrontations. Data stem from document studies and participant observation on all basic firearms courses. Findings show similarities regarding the safety, firearms handling and marksman skills that recruits/students need to have to pass their qualification tests, and the absence of policies for basic firearms training. Distinct differences are the way instructors can access and make use of documented experiences of real-life firearms incidents, and the shooting targets used. For both countries, a key finding is that the firearms training context reflects, to a limited extent, performance environments of real-life armed confrontations. Thus, findings of this study indicate a need for the firearms training itself to be improved, or additional training added, to enhance safe and effective handling of real-life firearms confrontations.